myc Gene and Cancer Variant Analysis and Network Interaction: An In-Silico Analysis - Saeed M Kabrah; Talal Qadah; Arwa F Flemban (Indian Journal of Forensic Medicine & Toxicology, 2022)
The myc is a proto-oncogene that regulates the cellular process like cell growth, proliferation,metabolism, apoptosis and malignancy pathologies. myc deregulation occurs in several cancers andplays a significant role in disease development, metastatic potential, and therapeutic resistance. Drugtargeting myc in cancer remains highly desirable with substantial challenges, delaying the direct myctargeted drugs’s development. These drugs target the myc transcriptions deregulations in tumours cellby compound inhibiting the inducing of epigenetic silencing or regulation of G-quadruplex structureswithin the myc promoter. Proteins involved in myc’s post-translational modulation have been identifiedas significant surrogate targets for lowering myc activity downstream of aberrant cell stimulatorysignals.